PEMASARAN BERBASIS HUBUNGAN PADA KERJASAMA PERGURUAN TINGGI NEGERI: KASUS INSTITUT PERTANIAN BOGOR - Dwi RachmawatiI, Sonya; mulyati, heti; simanjuntak, megawati (TADBIR MUWAHHID, 2019)
IPB University should implement its function: teaching, research and community services through collaboration with external partners, especially in national scope. However, the Memorandum of Understanding sometimes did not follow by concrete programs. In addition, the university should maintain string relationship to improve it partner’s commitment. Therefore, it is necessary to analyze the factors of relationship marketing to IPB’s partners. This study used survey methods to 100 respondents with questionnaire as the tool. The study used descriptive analysis to describe partner profiles and answers with top three boxes method. The results identified that based on location, partners were concentrated in Java with the most types of institutions are district and city governments. Cooperation initiators generally come from partners. The maximum duration of cooperation is 1-5 years. Number of collaboration 1-5 activities dominate partners. In general, partners are still actively collaborating with IPB, with more active MoU compared to those that are non-active. Trust has the highest perception value of respondents and followed by communication and shared values. Partner's perception of commitment to cooperation and satisfaction is good, while the benefits of cooperation are categorized sufficient. The variable relationship benefits need to be of concern to IPB and be improved by increasing competencies, human resources and appropriate technology that are applicable to the industrial world and local governments.